If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + (1 + m) + -6 = 18 Remove parenthesis around (1 + m) 18 + 1 + m + -6 = 18 Reorder the terms: 18 + 1 + -6 + m = 18 Combine like terms: 18 + 1 = 19 19 + -6 + m = 18 Combine like terms: 19 + -6 = 13 13 + m = 18 Solving 13 + m = 18 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + m = 18 + -13 Combine like terms: 13 + -13 = 0 0 + m = 18 + -13 m = 18 + -13 Combine like terms: 18 + -13 = 5 m = 5 Simplifying m = 5
| 4+y=95 | | (2x+4)+(x-12)+(x+9)+(3x-33)=360 | | 8s^2+22s-21=0 | | 47=-17-n | | -2x(-2)=3x(-7) | | -1.3x+.4=-1.16 | | 3(6x-6)=4(9-9x) | | 5(x-5)-8x=-28 | | 8x^2=500+3x^2 | | 9x+3=8whatisx | | 4-5(3t+3)= | | 2n+3n=228 | | 108+(5x+27)+(4x+3)+69=360 | | 5q+8=4q | | 1.3x+0.4=-1.16 | | 3x+6+4y+7=30 | | 1n+2n+3n=228 | | 9.7-16.1=0 | | 5.9n-2.52n=-13.0468 | | 8n-7=5n+32 | | 5m=4m-10 | | 3.5x+5.11x=-17.22 | | 2x^2+19x=180 | | 9y+9-3y=2y+4 | | 8(4y-5)=3y+5y | | [-6+(-13)]+8=-6+(m+8) | | 11-4p=-5(p-1) | | -8a-2(2a-1)=-40+2a | | 3.2+0.17-w=5.75 | | 5v+18=2(8v-2) | | 92+2x=78+3x | | 86=32+6(x-2) |